miRNA and lncRNA gene variants in Autism Spectrum Disorder - Marques, Ana Rita (2018)
Autism Spectrum Disorder (ASD) is a clinically heterogeneous neurodevelopmental disorder. Genetic factors are estimated to account for 50 to 80% of the familial ASD risk, but most of the genetic determinants are still not known and a role for epigenetic factors is likely. In this study we explored the potential role of noncoding RNAs in ASD by comparing the frequency of Copy Number Variants (CNVs) targeting microRNA (miRNA) or long noncoding (lncRNA) genes in ASD patients (n=3570) with control subjects (n=9649), using the Fisher’s exact test corrected for multiple testing. We found 22 miRNA genes exclusively targeted by CNVs in ASD subjects and 14 miRNA genes more frequently disrupted by CNVs in ASD patients than in controls. Two miRNA were previously associated with ASD in serum miRNA profiling studies, while 5 novel miRNAs for ASD have been described in schizophrenia, a disorder that phenotypically and genetically overlaps with ASD. Many putative targets of these 36 miRNAs are reported ASD risk genes. Gene-target enrichment analysis identified 6 significant pathways, 2 of which, the PI3K-Akt and MAPK signalling pathways, have been implicated in ASD. We further identified 102 novel lncRNA genes more frequently targeted by CNVs in ASD, 3 of which are antisense to ASD candidate genes. These results support our hypothesis that genetic variants targeting noncoding regulatory RNAs are involved in ASD pathophysiology. This systems biology integrative strategy will provide a better understanding of the biological processes underlying ASD, and contribute to biomarker and drug target discovery.